Assessment of newborn screening in the public health system of a municipality in northern Rio Grande do Sul - Tonon, Tássia; Sisti, Elisa; Nalin, Tatiéle; Schwartz, Ida Vanessa Doederlein (Clinical and Biomedical Research, 2018)
Introduction: Newborn screening allows the screening of diseases that are still in the asymptomatic period and whose early diagnosis and treatment are associated with reduced infant morbidity and mortality. The aim of this study was to evaluate the public National Newborn Screening Program in the municipality of Carazinho, state of Rio Grande do Sul (RS), Brazil. Methods: This was a population-based, retrospective, descriptive study. We collected and transcribed data from a database of the Carazinho municipal laboratory, which is affiliated with the referral center for newborn screening in RS. The records of all individuals undergoing newborn screening from 2005 to 2010 were reviewed, and information was collected on the program coverage, time elapsed between birth and screening (first collection), and test results. Results: The program had a coverage of 75.5%. One suspected case of phenylketonuria, three suspected cases of congenital hypothyroidism and no suspected cases of hemoglobinopathy were identified. In addition, there were 18 positive results for hemoglobin S heterozygosity, five for hemoglobin D heterozygosity, two for hemoglobin C heterozygosity, and one for a rare variant hemoglobin. When analyzing the newborn’s age at the time of blood collection, it was observed that 63.1% were within the recommended age range. Conclusion: Our findings suggest the need for optimization of public newborn screening in the evaluated municipality. The strategies to be adopted should include education of the population and especially of managers and health professionals about the importance of newborn screening. Keywords: Newborn screening; public health; mass screening